Synthesis and Characterization of Novel Nanodiopsidebioceramic Powder - L. Ghorbanian; R. Emadi; M. Razavi; H. Shin; A. Teimouri (Journal of Nanostructures, 2012)
Diopside  has  been  successfully  prepared  by  a  modified  sol-gel method.Optimization  in calcination temperature and mechanical ball milling  resulted  in  a  pure  and  nano-sized  powder  which characterized by means of scanning electron microscopy (SEM), X- ray diffraction (XRD), transmission electron microscopy (TEM) and fourier  transform  infrared  Spectroscopy  (FT–IR). We  hypothesized that  nano-sized  diopside  would  mimic  more  efficiently  the nanocrystal  structure and  function of natural bone apatite, owing  to the  higher  surface  area,  compare  to  conventional  micron-size diopside.  Accordingly,  we  used  the  unique  advantage  of nanotechnology  to  improve  novel  nanodiopside  particles  as  a potential  candidate  for  bone  tissue  regeneration  whether  as  a  peri- implant filling powder or in combination with other biomaterials as a composite scaffold.